2017
DOI: 10.32404/rean.v4i5.2192
|View full text |Cite
|
Sign up to set email alerts
|

COINOCULAÇÃO DE Bradyrhizobium japonicum e Azospirillum brasilense EM SEMENTES DE AMENDOIM DE DIFERENTES TAMANHOS

Abstract: O tamanho da semente é um importante indicador físico da qualidade fisiológica das sementes, pois pode afetar a taxa de germinação e o crescimento inicial das plântulas. Neste contexto, o presente estudo teve como objetivo avaliar os efeitos do tamanho das sementes e da inoculação de Bradyrhizobium japonicum e Azospirillum brasilense de forma isolada ou combinada na emergência das plântulas, nodulação das raízes e no crescimento inicial das plantas de amendoim (Arachis hypogaea L., cv. IAC Tatu ST). As plantas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
1
4
0
8
Order By: Relevance
“…The inoculation with A. brasilense alone was not an efficient agronomic practice because it resulted in grain yield equivalent to the non-inoculated plants in both growing seasons (Table 3). Similar results were reported by Silva et al (2017) in peanuts, who found that the inoculation with A. brasilense alone did not significantly affect nodulation and plant growth. These results show that leguminous plants are dependent on the inoculation of symbiotic bacteria (rhizobia), and inoculation of non-symbiotic bacteria (i.e., A. brasilense) alone has no beneficial effect on nodulation, plant growth, and crop yield.…”
Section: Inoculation Treatmentsupporting
confidence: 89%
See 2 more Smart Citations
“…The inoculation with A. brasilense alone was not an efficient agronomic practice because it resulted in grain yield equivalent to the non-inoculated plants in both growing seasons (Table 3). Similar results were reported by Silva et al (2017) in peanuts, who found that the inoculation with A. brasilense alone did not significantly affect nodulation and plant growth. These results show that leguminous plants are dependent on the inoculation of symbiotic bacteria (rhizobia), and inoculation of non-symbiotic bacteria (i.e., A. brasilense) alone has no beneficial effect on nodulation, plant growth, and crop yield.…”
Section: Inoculation Treatmentsupporting
confidence: 89%
“…Peres et al (2016) measured the increase in bean nodulation of 149%, using the co-inoculation with R. tropici and A. brasilense compared to the inoculation with R. tropici alone. Similarly, Silva et al (2017) reported that inoculation of Bradyrhizobium japonicum combined with A. brasilense resulted in an increase in the peanut nodulation of 56% compared to inoculation of B. japonicum alone. This increase in root nodulation with co-inoculation may have been due to the synergistic effect of rhizobia and azospirilla bacteria in improving the formation of root nodules in leguminous plants.…”
Section: Causes Of Variationmentioning
confidence: 90%
See 1 more Smart Citation
“…Entre os promotores de crescimento vegetal, os microrganismos do grupo dos rizóbios, além de serem eficientes fixadores de nitrogênio, também são capazes de promover o crescimento de não-leguminosas por meio de diversos mecanismos, como a produção de hormônios (Chen et al, 2005;Schlindwein et al, 2008;Silva et al, 2017). Fungos do gênero Trichoderma são capazes de colonizar raízes de diversas espécies de plantas de interesse econômico, podendo estimular o crescimento vegetal (Bettiol et al, 2012;Stefanello e Bonett, 2013;Fragoso e Custódio, 2016).…”
Section: Introductionunclassified
“…Em relação ao desenvolvimento das plantas do feijoeiro, o cultivo em semeadura convencional aumentou, respectivamente, em 24,3% e 11,1% a massa da matéria seca da parte aérea das plantas cultivadas nas safras "da seca" e "do inverno" e em comparação às plantas cultivadas em semeadura direta (Tabela 3). De acordo com , a soja (HUNGRIA et al, e 2015CHIBEBA et al, 2015) e o amendoim (SILVA et al, 2017).…”
Section: Para O Controle E a Prevenção De Colletotrichum Lindemuthianunclassified